Enhancement in Bioaccessibility and Bioavailability of Phenolic Compounds during Black Glutinous Rice Tape Fermentation - Azkia, Mita Nurul; Setyaningsih, Widiastuti; Mayangsari, Yunika; Cahyanto, Muhammad Nur (agriTECH, 2024)
Black glutinous rice (Oryza sativa var. glutinosa) tape fermented with various yeast, mold, and bacteria is often rich in phenolics compounds and can contribute positively to health through its antioxidants activity. Despite the potential, these compounds have limited bioavailability value due to their structure, degree of glycosylation or polymerization, and interactions with other components. Therefore, this study aims to determine the effect of fermentation on bioavailability and bioaccessibility of phenolics compounds in black glutinous rice tape. During the procedures, cooked black glutinous rice was inoculated with ragi tape for 72 hours. Sampling was then performed every 24 hours to analyze bioaccessibility of phenolics compounds, flavonoids, and antioxidants activity. Subsequently, absorption was carried out using an everted gut sac model. The results showed that phenolics compounds were released from the food matrix during gastric and small intestine digestion. Fermentation was shown to increase the content of accessible phenolics compounds from 19.89% to 27.31%, flavonoids from 68.88% to 81.72%, and antioxidants activity from 13.56% to 22.89%. During fermentation, the highest increments were obtained after 72 hours, with 27.31% for total phenolics compounds, 81.72% for flavonoid compounds, and 22.89% for antioxidants activity. The products obtained after 72 hours of fermentation exhibited significantly highest absorption, but no significant differences were observed between the duodenum and ileum segments. The absorption of these compounds in the jejunum from the extract was significantly higher in fermented samples. Therefore, fermentation significantly enhanced bioavailability of phenolics compounds in black glutinous rice tape.